Cacat Kehendak Yang Lahir Dari Hubungan Kontraktual Beserta Akibat Hukumnya - Yahman (Fakultas Hukum Universitas Bhayangkara Surabaya, 2010)
The contract is a legal relationship agreement between the two sides within the framework of business activities. In Article 1320 Civil Code define the terms of a contract valid, namely: the existence of an agreement between parties to bind themselves; skill in making the contract; a certain thing; a cause that is allowed. The first two conditions (the existence of an agreement and kecapakan act) is called as a requirement, subjektif, because of the subject contract, while the second two conditions (a certain thing and because that allowed) is called the terms, because it involves the object of the contract.